THE EFFECTS OF COOPERATIVE LEARNING MODEL TYPE GROUP INVESTIGATION (GI) AND MASTERY MATTER PHYSICS PREREQUISITES PHYSICS TOWARDS STUDENTS LEARNING OUTCOMES SMA - Mutiara . (Jurnal Pendidikan Fisika, 2014)
The purposes of the research are: To determine differences in learning outcomes of students with learning model Cooperative Group Investigation and Direct Instruction teaching model, to determine differences in learning outcomes student's mastery of the material that has low prerequisite Physics and Physics prerequisite mastery high, to determine the interaction between Models of Learning and the level of mastery learning model materials physics prerequisite in improving student learning outcomes Physics. The sample in this study conducted in a cluster random sampling of two classes, where the first class as a class experiment applied learning models Cooperative Group Investigation as a class and the second class of controls implemented Direct Instruction model. The instrument is used in this study is physics learning outcomes tests in narrative form as many as 10 questions and materials physics prerequisite mastery tests in narrative form as many as 7 questions that have been declared valid and reliable. The results were found: there are differences in physical students learning outcomes are taught by Cooperative Group Investigation learning model and Direct Instruction teaching model. There is a difference in student's learning outcomes that have a low mastery of prerequisite Physics and Physics prerequisite mastery of the material is high. There is interaction between learning models and the level of student mastery of the material prerequisites of Physics in influencing the physical students learning outcomes.